Edukasi dan Skrining Gizi Interaktif Melalui Permainan dalam Pembentukan Generasi Lancang Kuning: Upaya Pencegahan Stunting Pada Remaja - Masrinah Munawarah Tampubolon; Nurhannifah Rizky Tampubolon; Al Aminuddin Syakhira Zulien; Nurul Zahidah (Unri Conference Series: Community Engagement, 2025)
Adolescents represent a strategic group in the prevention of intergenerational stunting, particularly in Pekanbaru, which faces nutritional and health behavior challenges. This community engagement initiative is part of the Generasi Lancang Kuning program, aimed at fostering healthy and empowered youth through educational approaches. The intervention included nutrition education via interactive games and training in nutritional status screening for junior high school students. Pre-test results indicated that adolescents had a high level of nutritional knowledge (76.67%), with an average score of 11,23. An 8.64% rise in the average score reflects the effectiveness of the learning approach implemented, suggesting enhanced literacy and engagement among participants. Nutritional status data revealed that 47% of participants were underweight and 13% were obese. Participants demonstrated the ability to conduct nutritional screenings and categorize their peers’ nutritional status independently. Through the “Isi Piringku” game, they also showed competence in selecting food items that meet balanced nutrition criteria. Evaluation findings suggest that game-based methods enhanced adolescents’ understanding and boosted their confidence in disseminating nutritional information among peers. These capabilities are expected to support their continued role as peer educators within the Generasi Lancang Kuning program, contributing to promotive and preventive efforts to reduce stunting risk among adolescents.